The role of laboratory activities in aerospace control education: two case studies. Issue 2 (2020) - Giurato, Mattia; Invernizzi, Davide; Panza, Simone; Lovera, Marco
Abstract: Aerospace control education can significantly benefit from actual hands-on experience. In most cases, however, such experience can only be provided to students in small-scale project activities. In this paper the experience gathered in integrating laboratory activities in aerospace control education in the UAV Lab and in the Advanced Aerospace Control courses is presented and discussed. UAV Lab is an extra-curricular course aimed at an interdisciplinary group of students covering the whole design cycle for a multirotor UAV, from conceptual design to in-flight validation, with specific emphasis on hands-on experience in hardware/software integration, data collection and analysis and flight testing. Advanced Aerospace Control, on the other hand, is a curricular Master course in robust and nonlinear control, in the framework of which students are requested to solve a control design problem formulated over the dynamics of a multirotor UAV. The paper presents the course syllabi, discusses the role of laboratory activities and provides an overview of the obtained results.